A facile method for fabrication of large area graphene nanostructures. Issue 11 (2nd November 2017) - Kuru, Cihan; Jin, Sungho
ABSTRACT: In this study, we introduce a novel method to produce large area interconnected graphene nanostructures. A single layer CVD (Chemical Vapor Deposition) grown graphene was nanostructured by employing dewetted Ni thin film as an etching mask for the underlying graphene. As a result, a network of graphene nanostructures with irregular shapes and widths down to 10 nm is obtained. The FET (field effect transistor) devices fabricated employing the nanostructured graphene as channel material exhibit increased on/off current ratio compared to pristine graphene indicating a slight band gap opening due to the quantum confinement effect in such narrow graphene nanostructures. This technique can be useful for the large scale fabrication of graphene based electronic devices such as FETs and sensors.